Heat shock protein 70 dampens the inflammatory response of human PDL cells to mechanical loading in vitro. (13th March 2019) - Marciniak, Jana; Lossdörfer, Stefan; Kirschneck, Christian; Deschner, James; Jäger, Andreas; Wolf, Michael
Abstract : Background and objective: Previously, we demonstrated an inflammatory response of human PDL (hPDL) cells to mechanical loading. The cellular reaction was dampened by heat pre‐treatment suggesting a protective role for heat shock proteins (HSP) during stress‐induced ischemia. Here we explored if HSP70, which has already been documented in the pressure zone of tooth movement, might be regulatorily involved in the attenuation of the inflammatory response. Materials and methods: Fifth passage hPDL cells were mechanically loaded in the presence of the HSP70 inhibitor VER155008. Cell morphology, HSP70 expression, viability, IL‐6 and IL‐8 expression were determined by means of microscopy, realtime‐PCR and ELISA. The conditioned medium of mechanically loaded and pre‐treated hPDL cells was used to culture monocytes to identify a potential impact on adhesion and osteoclastic differentiation capacity. Results: Mechanical cell stress resulted in a significant increase of pro‐inflammatory parameters. HSP70 inhibition led to a further enhancement of cytokine expression. The conditioned medium of mechanically loaded hPDL cells significantly increased monocyte adhesion and differentiation along the osteoclastic pathway. VER155008 pronounced this effect significantly. Conclusion: The results indicate a regulatory role for HSP70 in the control of the inflammatory hPDL cell response to mechanical loading and identify HSP70 as a target in the attempt to attenuate tissue damage during orthodontic tooth movement. Furthermore, the present findings point to the risk of increased periodontal destruction when medication targeting HSP70 is applied for severe medical conditions during orthodontic tooth movement.